Development of a liquid chromatographic method with a different selectivity for the quantification of eighteen phytocannabinoids in hemp - Liguo Song; Jake Provis; Ammar Mohammad Al-Bataineh; Keszia Jervelle Fabien; Madeline Kotler (Talanta Open)
To quantify phytocannabinoids in hemp, liquid chromatography diode array detector (LC-DAD) methods are favored, but their selectivity depends on baseline separation of all phytocannabinoids and unknown compounds in an extract. Therefore, development of a LC-DAD method with a different selectivity has become highly desirable. Currently, most LC-DAD methods use the water/acetonitrile eluting system, while this study aimed to use the water/methanol eluting system. A systematic investigation of various chromatographic parameters on LC separation of eighteen phytocannabinoids, the maximum number that has been quantified in hemp so far, plus two potential internal standards, led to a four-step isocratic mobile phase that was able to baseline separate the twenty compounds with a significantly different eluting order from published methods. Although changes in the mobile phase composition caused baseline drifts, consequent difficulty in quantification was avoided through detection at wavelengths longer than 230 nm. Subsequently, the method was validated according to the ISO 17025 guidelines, calibrated between 0.04 and 50 µg/mL, and used to analyze phytocannabinoids in nine strains of hemp flowers that were extracted using methanol between 0.04 and 50 % (w/w). Extraction recovery was tracked in real-time by spiking one of the two potential internal standards, i.e., abnormal cannabidiol (ACBD), a cannabinoid not naturally present in hemp. Method selectivity was further assessed by electrospray ionization time-of-flight mass spectrometry (ESI/TOFMS), indicating minimum interferences. In addition, five untargeted/unknown phytocannabinoids were identified by ESI/TOFMS, including two structural isomers of Δ9-tetrahydrocannabinol (Δ9-THC), two structural isomers of Δ9-tetrahydrocannabinolic acid (Δ9-THCA), and one structural isomer of Δ9-THC acetate.